Assistance in Management and Technology-Based Mosque Digitalization to Improve the Quality of Community Services - Kirom, Cihwanul; Cahyadi, Iwan Fahri; Afandi, Johan; Adni, Riyan; Cahya, Bayu Tri; Muflih, Betania Kartika (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to improve the quality of mosque management and operations, utilizing digital technology to strengthen the relationship with the congregation. The methods used in these activities included educational methods, training, and mentoring. The target of this community service activity was the imams and takmirs in Kudus Regency, in optimizing administrative tasks and activities. The evaluation process for this community service activity involved assessing coordination, planning, surveys, training, and digital technology implementation to ensure effective mosque management. It includes analyzing data from each stage, quantitatively and qualitatively, to identify trends, challenges, and successes. The results of this service showed that had significantly enhanced the quality of community service. Mosque administrators and religious institution managers adopted digital solutions using the masjidkudus.com application, enhanced religious activity monitoring, and improved communication with worshippers via the website. These activities raised awareness about the importance of digitalization, paving the way for mosques to become centers of education and communication, ensuring sustainability and benefit for the Muslim community in Kudus.